Glycoprotein IIb/IIIa Receptor Antagonist Tirofiban Inhibits Thrombin Generation during Cardiopulmonary Bypass in Baboons - Rao, A. Koneti; Sun, Ling; Hiramatsu, Yugi; Gorman, Joseph H., III; Edmunds, L. Henry, Jr. (Thrombosis and Haemostasis, 1999)
Platelets play a major role in coagulation mechanisms and anti-GPIIb-IIIa antibodies inhibit tissue-factor induced thrombin generation in in vitro studies. Tirofiban, a nonpeptide selective glycoprotein (GP) IIb/IIIa antagonist, preserves platelet number and function during cardiopulmonary bypass (CPB) in baboons. We tested the hypothesis that platelet inhibition by tirofiban inhibits thrombin generation in vivo. Four groups of baboons (n = 7-12) were perfused for 60 min; all groups received heparin (300 units/kg). The controls received only heparin. The low dose (0.1 μg/kg/min) and high dose (0.3 μg/kg/min) infusion groups received tirofiban for 60 min before and 60 min during CPB. The bolus plus low dose infusion group received a 15 μg/kg bolus before starting CPB and a low dose infusion (0.1 mg/kg/min) only during CPB. At end of CPB, compared to control group (2.99 ± 0.36 nM), prothrombin fragment F1.2 levels were lower (p <0.05) in low dose infusion group (1.65 ± 0.14 nM, mean ± SE) and high dose infusion group (1.71 ± 0.19 nM), but not bolus plus infusion group (2.69 ± 0.49 nM); they remained significantly lower after protamine administration. At end of CPB, thrombin-antithrombin complex levels were lower in high dose infusion group (40.0 ± 11.2 ng/ml, p <0.05) compared to control group (76.2 ± 7.3 ng/ml). These studies indicate that tirofiban inhibits not only platelet aggregation but also thrombin generation in vivo during CPB, and that this effect is demonstrable even in the presence of intense heparin anticoagulation. They underscore the important inhibitory effect of GPIIb-IIIa antagonists on thrombin generation.